PV Module Surface Area Maximisation for Enhancing Performance - Moses Oyaro Okello (Revue des Énergies Renouvelables, 2025)
The amount of solar energy produced is directly proportional to the surface area of PV module exposed to solar irradiance. To increase the productivity of PV module, a number of techniques are proposed by curving the surface or protruding the PV module surface to maximise the surface area. The geometrical design analysis showed that, depending on the chosen surface curving method, the PV module can achieve a remarkable increase in surface area.